1987
DOI: 10.1007/bf00032315
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast biogenesis at cold-hardening temperatures. Development of photosystem I and photosystem II activities in relation to pigment accumulation

Abstract: Chloroplast biogenesis during continuous illumination at either low, cold-hardening temperatures (5°C) or non-hardening temperatures (20°C) was examined by monitoring the etioplast-chloroplast transformation with respect to pigment accumulation and the development of PSI- and PSII-associated electron transport activities in winter rye (Secale cereale L. cv Puma). Generally, chlorophyll and carotenoid accumulation during greening at 20°C were characterized by rapid initial rates in contrast to pronounced, initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
16
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 19 publications
6
16
0
Order By: Relevance
“…First, although greening at low irradiance indicated minimal differences in chloroplast biogenesis based on the disappearance of PORA and the appearance of Lhcb2 in the wild type and im (Figure 9C), the accumulation of Lhcb2, PsaB, and PsbA were delayed and the relative abundance of these thylakoid proteins was reduced in im cotyledons relative to the wild type during greening at 150 mmol photons m 22 s 21 ( Figure 9C; see Supplemental Figure 5 online). Furthermore, the observed kinetics for the disappearance of PORA and the appearance of PsaB, PsbA, and and Lhcb2 during the greening of wild-type Arabidopsis cotyledons are consistent with those published for chloroplast biogenesis in other photoautotrophs (Krol et al, 1987;Biswal et al, 2003;Philippar et al, 2007;Sakamoto et al, 2008).…”
Section: Discussionsupporting
confidence: 77%
“…First, although greening at low irradiance indicated minimal differences in chloroplast biogenesis based on the disappearance of PORA and the appearance of Lhcb2 in the wild type and im (Figure 9C), the accumulation of Lhcb2, PsaB, and PsbA were delayed and the relative abundance of these thylakoid proteins was reduced in im cotyledons relative to the wild type during greening at 150 mmol photons m 22 s 21 ( Figure 9C; see Supplemental Figure 5 online). Furthermore, the observed kinetics for the disappearance of PORA and the appearance of PsaB, PsbA, and and Lhcb2 during the greening of wild-type Arabidopsis cotyledons are consistent with those published for chloroplast biogenesis in other photoautotrophs (Krol et al, 1987;Biswal et al, 2003;Philippar et al, 2007;Sakamoto et al, 2008).…”
Section: Discussionsupporting
confidence: 77%
“…Thus, the increased capacity for PSI electron transport under cold-hardening conditions appears to be a general phenomenon observed under natural and controlled environment conditions. Krol et al (9) recently suggested that the increased PSI activity observed after growth of winter rye, an annual, at cold-hardening conditions was a consequence of thylakoid biogenesis at low temperature. Although periwinkle thylakoids exhibit a twofold increase in PSI activity upon exposure to winter conditions, the overwintering leaves had developed and become fully expanded during the warm spring and summer months.…”
Section: Resultsmentioning
confidence: 99%
“…They suggested that this altered assembly pattern at 5°C results in a change in the organization of PSI which, in turn gives rise to the increased capacity for PSI electron transport (9). In contrast, the pattern for development of PSII electron transport was similar at both 5 and 20°C (9). Low temperature growth did not affect the apparent quantum efficiencies of whole chain, PSI, or PSII electron transport (7).…”
mentioning
confidence: 96%
See 2 more Smart Citations